High-speed electrodeposition for Cu pillar fabrication and Cu pillar adhesion to an Ajinomoto build-up film (ABF). (August 2021) - Lee, Pei-Tzu; Chang, Chih-Hao; Lee, Cheng-Yu; Wu, Ying-Syuan; Yang, Cheng-Hsien; Ho, Cheng-En
Graphical abstract: Highlights: High-speed electrodeposition technology for efficient Cu pillar adhesion. Current density dominated the Cu microstructure, pillar morphology and its adhesion. Finite element analysis of high-speed electrodeposition. Enhancement of electrolyte circulation can greatly facilitate electrodeposition. Abstract: The fabrication of Cu pillars has recently attracted much attention from the microelectronic/communication industry because pillars can act as thermal dissipation devices and electrical interconnections among different packaging levels, providing efficient utilization of space in microelectronic packaging applications. This study was conducted to investigate the fabrication of Cu pillars through a high-speed electrodeposition method and their adhesion to an Ajinomoto build-up film (ABF). The morphological, crystallographic, electrical, and mechanical characteristics of the Cu pillars electroplated with various current densities ( j = 2, 5, 7.5, and 10 A/dm 2 ) were systematically investigated through a scanning electron microscope (SEM) combined with electron backscatter diffraction (EBSD) analysis system, field-emission transmission electron microscope (FE-TEM), an ohm meter, and a nanoindenter. Additionally, the adhesion of the Cu pillars to an ABF substrate after high-temperature storage was evaluated via a shear test. Finally, a finite element analysis (FEA) method (COMSOL-Multiphysics) was employed to simulate the current density and electrolyte distributions in a via structure upon high-speed Cu electrodeposition to characterize the morphological/crystallographic/mechanical transitions induced by increasing j . This valuable information advances our understanding of electrochemical metal deposition and would be helpful in the development of high-speed Cu electrodeposition technology.